2014
DOI: 10.4085/1062-6050-49.2.13
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Practice Educational Intervention for Athletic Trainers: A Randomized Controlled Trial

Abstract: An educational intervention consisting of 10 Web-based modules was an effective mechanism to increase knowledge of foundational EBP concepts among ATs. However, it is not known whether ATs are integrating EBP into daily clinical practice. Researchers should determine whether increased knowledge of EBP affects the daily clinical decision making of ATs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 30 publications
1
57
0
Order By: Relevance
“…28,29 Therefore, based on a predetermined set of criteria, we selected participants who would provide the most valuable insight into the research aims. To be considered as viable candidates for this study, ATs had to have participated in the experimental group of a previous study 15 and had to have accessed all 10 Web-based learning modules, which was determined through the Web-based module usage data sheet that the NATA office provided. Stratified purposeful sampling, sometimes considered as a sample within samples, allowed us to capture major variations that might occur across a population.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 Therefore, based on a predetermined set of criteria, we selected participants who would provide the most valuable insight into the research aims. To be considered as viable candidates for this study, ATs had to have participated in the experimental group of a previous study 15 and had to have accessed all 10 Web-based learning modules, which was determined through the Web-based module usage data sheet that the NATA office provided. Stratified purposeful sampling, sometimes considered as a sample within samples, allowed us to capture major variations that might occur across a population.…”
Section: Participantsmentioning
confidence: 99%
“…30 To ensure a true representativeness of the athletic training population, we invited an equal number of clinicians and educators to participate in this study. 24 Eighty-nine of the 164 ATs who accessed the Web-based modules in the previous investigation 15 met the predetermined criteria for this study. The research team confirmed data saturation of both branches of the interview protocol after 25 ATs (14 women, 11 men; athletic training experience ¼ 16.00 6 9.41 years) had been interviewed.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research [10][11][12][13][14] in athletic training shows that foundational knowledge of EBP concepts is low. Stand-alone workshops, journal clubs, and clinically integrated teaching improve knowledge of EBP and critical appraisal in medicine, 15 whereas web-based modules increase foundational EBP knowledge in athletic trainers (ATs).…”
Section: Athletic Trainers' Current Knowledge and Envisioned Use Of Fmentioning
confidence: 99%
“…Stand-alone workshops, journal clubs, and clinically integrated teaching improve knowledge of EBP and critical appraisal in medicine, 15 whereas web-based modules increase foundational EBP knowledge in athletic trainers (ATs). 12,14 In addition to knowledge, information has been previously disseminated regarding barriers to use and implementation of EBP. [16][17][18][19][20][21] Although valuable in content, these previous studies were conducted before the implementation of the BOC requirement regarding EBP continuing education.…”
Section: Athletic Trainers' Current Knowledge and Envisioned Use Of Fmentioning
confidence: 99%